Pembuatan Sumur Resapan Air Hujan untuk Mitigasi Banjir di Kawasan Perumahan Karangpucung, Purwokerto Selatan - Susatyo Adhi Pramono; Endang Sri Wahyuningsih; Iwan Rustendi; Heru Bayuaji Sanggoro; Muhammad Edwin Rachmanudin (Yayasan Literasi Sains Indonesia, 2025)
The Karangpucung Housing Area in Purwokerto Selatan District frequently faces local flooding problems due to increased rainfall intensity and limited water absorption areas caused by urbanization. This condition is further exacerbated by the community’s lack of understanding regarding the importance of water conservation and simple technologies for flood mitigation. To address this issue, this community service activity was conducted with the aim of providing education and concrete action through socialization and the construction of rainwater infiltration wells. The activity was carried out from April to May 2025 using the Participatory Rural Appraisal (PRA) approach and a community-based approach to encourage active community involvement. The activity stages included site surveys, socialization and outreach, technical training on infiltration well construction, and monitoring and evaluation. The results showed that 50 residents actively participated in the socialization and training activities, and 10 infiltration wells were successfully built at strategic locations previously prone to flooding. Residents also demonstrated improved understanding of the function of infiltration wells and the importance of water conservation as part of hydrometeorological disaster mitigation. Testimonials from residents indicated a significant reduction in flooding following the well construction. This program demonstrates the effectiveness of an educational and participatory approach in encouraging behavioral change among the community. Moving forward, regular maintenance strategies and the involvement of other stakeholders are needed to ensure that this program can be replicated and expanded to other areas facing similar issues.